Intergenerational study: mirrors as a tool for self‐reflection. Issue 1 (2014) - ,
Abstract : Purpose – This qualitative study was an exploration on the process of self‐reflection on identity. The purpose of this paper is to see how mirrors could be used as a therapeutic tool and a meta‐physical bridge to one's inner consciousness.Design/methodology/approach – An intergenerational expressive arts group ( n =12) was organized around the question of identity. Following an open‐discussion around the topic of identity, participants were asked to decorate a mirror with words, images, and/or symbols while reflecting on the question, "Who am I?" A post‐session interview was conducted regarding participant's experiences during the creative process.Findings – The results indicated that mirrors can be used to connect to one's inner thoughts and feelings on the question of identity. Three core themes in the process of self‐reflection on identity were revealed which included introspection and self‐concern, connection and attachment to something or someone other than self, and taking action to help others.Research limitations/implications – This study was limited not only in size, but also in cultural diversity and disparity of age range. Although this study was limited, it provided a useful indicator for identifying core themes in the process of self‐reflection on identity.Originality/value – While there have been no studies on the therapeutic use of mirrors as a tool for self‐reflection and limited intergenerational studies with pre‐adolescent and adolescent students and older adults, results from this study will add to the body of expressive arts literature by providing a new metaphor for mirrors as a therapeutic tool for self‐reflection on identity. Acknowledgements : A version of this paper forms part of the author's PhD thesis at Lesley University. The mirrors in this intergenerational study can be viewed at: www.themirrorproject.com